2023
DOI: 10.1111/gtc.13051
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma‐derived G‐CSF promotes tumor growth and metastasis in mice through neutrophil recruitment and tumor cell proliferation, associated with poor prognosis of the patients

Abstract: Tumor‐derived G‐CSF is a well‐known factor to aggravate disease progression in various types of cancers. In this study, we investigated a role of G‐CSF in squamous cell carcinoma (SCC). High expression of G‐CSF in the tumor tissues of esophageal SCC (ESCC) patients correlated with poor prognosis. Murine SCC NR‐S1M cells produce considerable amount of G‐CSF, which expression is correlated with its metastatic potentials. Deletion of G‐CSF in NR‐S1M cells mitigated tumor growth and metastasis to lymph node and lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Recent studies have reported cases of positive anaplastic lymphoma kinase gene rearrangement [ 5 ] and resistance to PD-1/PD-ligand 1 inhibitors in G-CSF-producing spindle cell carcinoma [ 6 ]. In addition, G-CSF produced by NR-S1M cells in squamous cell carcinoma promotes tumor progression in mice through its bifunctional effects on neutrophil recruitment and tumor cell growth [ 7 ]. Therefore, reports on G-CSF-producing lung cancers are expected to increase in the field of lung cancer, where treatments, including gene therapy, are rapidly evolving.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported cases of positive anaplastic lymphoma kinase gene rearrangement [ 5 ] and resistance to PD-1/PD-ligand 1 inhibitors in G-CSF-producing spindle cell carcinoma [ 6 ]. In addition, G-CSF produced by NR-S1M cells in squamous cell carcinoma promotes tumor progression in mice through its bifunctional effects on neutrophil recruitment and tumor cell growth [ 7 ]. Therefore, reports on G-CSF-producing lung cancers are expected to increase in the field of lung cancer, where treatments, including gene therapy, are rapidly evolving.…”
Section: Discussionmentioning
confidence: 99%